Biological Approaches for Extraction of Bioactive Compounds From Agro-industrial By-products: A Review - Lemes, Ailton Cesar; Egea, Mariana Buranelo; Oliveira Filho, Josemar Gonçalves de; Gautério, Gabrielle Victoria; Ribeiro, Bernardo Dias; Coelho, Maria Alice Zarur (Frontiers in Bioengineering and Biotechnology, 2022)
Bioactive compounds can provide health benefits beyond the nutritional value and are originally present or added to food matrices. However, because they are part of the food matrices, most bioactive compounds remain in agroindustrial by-products. Agroindustrial by-products are generated in large quantities throughout the food production chain and can ─when not properly treated─ affect the environment, the profit, and the proper and nutritional distribution of food to people. Thus, it is important to adopt processes that increase the use of these agroindustrial by-products, including the biological approaches, which can enhance the extraction and obtention of bioactive compounds, which enable their application in the food and pharmaceutical industries. Biological processes have several advantages compared to non-biological processes, including the provision of extracts with high quality and bioactivity, as well as extracts that present low toxicity and environmental impact. Among biological approaches, extraction from enzymes and fermentation stands out as tools for obtaining bioactive compounds from various agroindustrial wastes. In this sense, this manuscript provides an overview of the main bioactive components found in agroindustrial by-products and the biological strategies for their extraction. We also provide information to enhance the use of these bioactive compounds, especially for the food and pharmaceutical industries.